Smart Skilling: Experimental Evidence on Vocational Training Design - Farzana Afridi; Tanu Gupta; Rachel Heath; Kanika Mahajan (Institute of Labor Economics (IZA), 2025)
We study how the design of vocational skill training programs impacts labor market outcomes, including occupational choice. Women applicants to skill training centres in India are randomized into either a vocational training (VT) program that combines sector-specific hard skills with on-the-job training, or VT plus Project-Based Experiential Learning that incorporates digital skills (VTP), or a control group which is not enrolled into any skill training. Almost a year after the start of the intervention, the nature of employment shifts towards the women's preferred sector, leading to higher self-employed work and earnings therein. These positive effects are observed only for the VTP group, whose usage of social media for business purposes increases due to the intervention. At the same time, satisfaction levels of women assigned to VTP training rise on multiple dimensions. Our findings highlight the role of complementary sector-specific skills in enhancing the impact of vocational training.
Keywords: J24; J44; J62; I31; 330; vocational skilling; digital skills; on-the-job training; self-employment; women; India